Temporal and spatial control of gene silencing in transgenic plants by inducible expression of double-stranded RNA - Sonnewald, Uwe; et al. (Plant Journal, 2003)
Downregulation of endogenous genes via post-transcriptional gene silencing (PTGS) is a key to the characterization of gene function in plants. The recent discovery that double-stranded RNA (dsRNA) is an extremely effective trigger of gene silencing greatly enhanced the predictability of this approach. However, strong constitutive silencing often leads to pleiotropic effects, which make it difficult to directly relate phenotype to gene function, or even interferes with the recovery of viable transgenic plants. Here, we show that strong genetic interference can be achieved in a chemically inducible fashion, allowing for temporal and spatial control of gene silencing in transgenic plants. To this end, transgenic tobacco plants were established expressing dsRNA in the form of intron-spliced hairpin structures under the control of the ethanol-inducible alc gene expression system. Targeting magnesium (Mg)-chelatase subunit I (Chl I) and glutamate 1-semialdehyde aminotransferase (GSA), both involved in chlorophyll (chl) biosynthesis, resulted in rapid and specific mRNA degradation upon induction with ethanol. Ethanol-inducible silencing of the target genes caused strong but transient phenotypical alterations featured by a progressive loss of chl in young leaves, which persisted for about 7-9 days before newly growing leaves completely recovered. About 10-30% of the primary transformants showed phenotype development upon induction. Local silencing of Chl I could be achieved by confined ethanol treatment of a single leaf without affecting any other part of the plant. Inducible gene silencing using the alc system promises to obviate the problems associated with constitutive RNA silencing and enables to dissect primary and secondary effects of PTGS at temporal and spatial resolution.
Keywords: chemically inducible expression; ethanol; double-stranded RNA; gene silencing; functional genomics; Nicotiana tabacum